Detection of the novel IMP-38 among carbapenemase-producing Enterobacteriaceae in a university hospital, China - Zijuan Jian; Yanming Li; Wenen Liu; Hongling Li; Yunli Zhang; Yanbing Li; Xiumei Gu; Wanchan Peng (Journal of Infection in Developing Countries)
Introduction: This study set out to investigate the molecular epidemiology of carbapenemase-producing Enterobacteriaceae isolates collected from Xiang Ya Hospital, Hunan, China. Methodology: The carbapenemase genes from Enterobacteriaceae isolates were determined by PCR and sequencing. Relatedness of Klebsiella pneumoniae isolates was evaluated by pulsed-field gel electrophoresis. Results: Twenty-four out of 738 non-repetitive Enterobacteriaceae isolates harbored carbapenemase genes including IMP-38, a novel IMP-type metallo-enzyme. Nine IMP-38-producing isolates were shown to originate from the same clone and caused a small outbreak in the neonatal ward. Conclusions: IMP-38, a novel IMP-type metallo-enzyme, was one of the predominant types of carbapenemase in the clinical carbapenem-resistant Enterobacteriaceae isolates in our hospital.